On the scorpion fauna of Egypt, with an identification key (Arachnida: Scorpiones). Issue 1 (2nd January 2018) - Badry, Ahmed; Younes, Mahmoud; Sarhan, Moustafa M. H.; Saleh, Mostafa
Abstract : The taxonomy and diversity of the scorpion fauna of Egypt was examined based on a large collection from most parts of the country and in view of recent revisionary systematics. We assessed the validity of listed records in light of new taxonomic findings and geographic distribution data and present a new list and an identification key to the scorpion fauna of Egypt consisting of 31 species, 18 of which were collected during this survey. Four species were not accepted for the list because no voucher material was available.